Development of Digital Book Bilingual Physics Learning Media Using Kvisoft Flipbook for High School Class X Semester 1 Subject of Newton's Law - Alga Nawangsih Fauziyah; Mohamed Ramadan; Phiwayinkosi Richmond Gumede; Idongesit N. Udosen (Journal of Educational Technology and Learning Creativity, 2023)
Purpose of the study: The purpose of this study was to develop learning media in the form of bilingual digital books on Physics learning materials on the subject of Newton's laws that meet the good criteria. Methodology: This research is a development research using mixed research methods with sequential exploratory design where the data obtained in this study are qualitative data supported by quantitative data. Sources of research data include material experts (content feasibility, language and images, presentation, and graphics), high school physics teachers as reviewers, and students who study making learning media as peer reviewers. Data analysis techniques used in this study are qualitative and quantitative analysis. Main Findings: Physics learning media in the form of digital books arranged according to the rules of writing modules on Newton's Law material and its application to State High Schools that have been developed, from all aspects meeting the very good criteria as many as 27 students out of 30 students. Then on good criteria as many as 3 students out of 30 students based on a questionnaire compiled according to the characteristics of the module according to the Ministry of National Education in 2008. Novelty/Originality of this study: The novelty of this research is that learning media have been developed in the form of digital books which are arranged according to the rules of writing modules on Newton's Law material and its application for class X high school with the manufacturing procedure using CorelDRAW X4 software in its manufacture.